1978
DOI: 10.1084/jem.147.4.1236
|View full text |Cite
|
Sign up to set email alerts
|

Role of viral infectivity in the induction of influenza virus-specific cytotoxic T cells.

Abstract: This report examines the requirement for infectious virus in the induction of influenza virus-specific cytotoxic T cells. Infectious influenza virus was found to be highly efficient at generating both primary and secondary cytotoxic T-cell response in vivo. Inactivated influenza virus however, failed to stimulate a detectable cytotoxic T-cell response in vivo even at immunizing doses 10(5)-10(6)-fold higher than the minimum stimulatory dose of infectious virus. Likewise inactivated virus failed to sensitize ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 35 publications
10
58
1
Order By: Relevance
“…It has also been demonstrated that active infection is not required for the induction of a CTL response to Sendai virus (25). However, sensitization of uninfected targets does not occur with UV-inactivated influenza virus (26), and other investigators suggested that synthesis of early viral proteins is needed for lysis of vaccinia-or ectromelia-infected targets (27,28). Thus, it appears that, in some systems, virus that is passively adsorbed to the cell surface is sufficient for cell lysis by sensitized CTLs whereas, in others, intracellular synthesis of viral proteins may be required.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been demonstrated that active infection is not required for the induction of a CTL response to Sendai virus (25). However, sensitization of uninfected targets does not occur with UV-inactivated influenza virus (26), and other investigators suggested that synthesis of early viral proteins is needed for lysis of vaccinia-or ectromelia-infected targets (27,28). Thus, it appears that, in some systems, virus that is passively adsorbed to the cell surface is sufficient for cell lysis by sensitized CTLs whereas, in others, intracellular synthesis of viral proteins may be required.…”
Section: Resultsmentioning
confidence: 99%
“…of BioQuest, Oxnard, Calif.) containing 15 ml of medium (22). The responder to stimulator cell ratio was 10:1.…”
Section: Gtntral Male Balb/c (H-2d) and Cba/h (H-mentioning
confidence: 99%
“…Viruses were assessed for serologic crossreactivity by the microtitration hemagglutination,inhibition test (22). Four HAU of a given virus in a volume of 0.025 ml PBS were added to serial twofold dilutions of each sera in a final volume of 0.025 ml in PBS.…”
Section: Gtntral Male Balb/c (H-2d) and Cba/h (H-mentioning
confidence: 99%
“…On transfer, virus-specific Tc cells afford protection against lethal influenza virus infection in mice (3,4) by clearing virus from the lungs (5,6). Any vaccine strategy to control influenza virus infection should therefore be designed to induce a long-lasting, crossreactive Tc memory population to protect against any new variants of A strain influenza viruses arising from either antigenic drift or shift.…”
Section: Introductionmentioning
confidence: 99%